Connectable : how leaders can move teams from isolated to all in - Jenkins, Ryan (Millennial keynote speaker); Van Cohen, Steven (McGraw-Hill, 2022)
"Expert advice on how to connect a lonely workforce-and improve employee engagement and productivity. When Covid-19 forced a sudden shift to remote work in 2020, it only exacerbated what had been a long-simmering issue in the workplace: Feelings of isolation and loneliness among employees are on the rise, and contribute to a real and growing mental health problem that affects both individuals and organizations. In Connectable, you'll learn how addressing the issues-and finding practical, effective solutions-can transform an isolated workforce to one that's happier, more engaged, and more productive in their efforts. With more than a decade spent helping companies lessen worker loneliness, Ryan Jenkins and Steve Cohen distill their methodology in these pages, showing you what's causing today's loneliness, the role inclusion plays in solving it, and how you can decrease loneliness and increase belonging, engagement, and performance with employees at every level-including yourself. You'll learn: How to develop emotional intelligence to show up for others, how to identify lonely or depressed employees, how to create psychological safety for employees, how to create environments of belonging and inclusion, how to create and cultivate connections across teams (in person or remote), how to create connected, driven, and high-performing teams using the 4-step Less Loneliness Framework, and more"--